Green algae (chlorophyta) of Tanjung Datu, Sarawak / I. Asmida, I. Ahmad and B. Halipah - I., Asmida; I., Ahmad; B., Halipah (2004)
In this present study, a tolal of 19 species of Chlorophyta, comprising of 9 families and 4 orders was recorded. Seaweeds of the order Bryopsidales was the most dominant in terms of species diversity since more than half of the total number of species (10 species) or 53% of the total species were from this order. On the other hand, Ulvales showed the least number of species since only 2 species or 11% were recorded. Most of the specimens were small in size, within the range of 1-8 cm, with an exception for Cladophora vagabunda. Marine macroalgae in Tanjung Datu were commonly found in the rock pools on dead corals and also on the sandy substrates. Five species of seaweeds from this study were new record for Malaysia. These species were Acetabularia roxasii, Anadvomene stellata, Bornetella oligospora, Dasycladus sp and Codium papillatum.